Vanadium nitride nanoparticle decorated N-doped carbon nanotube/N-doped carbon nanosheet hybrids via a C3N4 self-sacrificing method for electrochemical capacitors. Issue 24 (19th May 2022) - Liu, Jinghua; He, Xiong; Guo, Fei; Liu, Baosheng; Sun, Zijun; Zhang, Li; Chang, Haixin
Abstract : Vanadium nitride nanoparticle decorated N-doped carbon nanotube/N-doped carbon nanosheet hybrids have been fabricated for efficient supercapacitor. Abstract : Owing to the wide negative potential window (∼1.2 V) along with high specific capacitance (1340 F g −1 ) in alkaline electrolyte, vanadium nitride (VN) has been served as promising negative supercapacitor electrode material. However, VN is easy to dissolve during cycling process and shows low capacitance retainability. Herein, a hybrid electrode (marked as VN/NCNT/NCN), featuring VN nanoparticles and N-doped carbon nanotube inserted in N-doped carbon nanosheets, has been fabricated with a facile C3 N4 self-sacrificing method. The porous structure and high conductive carbon skeleton, as well as the uniform distribution of VN nanoparticles give VN/NCNT/NCN a great amount of active site and fulfill excellent electrochemical performance for VN/NCNT/NCN-based electrode. The as-fabricated hybrid electrode exhibits a maximum specific capacitance of 232.9 F g −1 at 1 A g −1 . Moreover, the cycling performance has been greatly improved and the specific capacitance remains 91% after 5000 cycles.